Metamorphic Evolution of Garnet-bearing Epidote-Barroisite Schist from the Meratus Complex in South Kalimantan, Indonesia - Nugroho Imam Setiawan; Yasuhito Osanai; Nobuhiko Nakano; Tatsuro Adachi; Amril Asy’ari (Geological Agency, 2015)
DOI:10.17014/ijog.2.3.139-156This paper presents metamorphic evolution of metamorphic rocks from the Meratus Complex in South Kalimantan, Indonesia. Eight varieties of metamorphic rocks samples from this location, which are garnet-bearing epidote-barroisite schist, epidote-barroisite schist, glaucophane-quartz schist, garnet-muscovite schist, actinolite-talc schist, epidote schist, muscovite schist, and serpentinite, were investigated in detail its petrological and mineralogical characteristics by using polarization microscope and electron probe micro analyzer (EPMA). Furthermore, the pressure-temperature path of garnet-bearing epidote-barroisite schist was estimated by using mineral parageneses, reaction textures, and mineral chemistries to assess the metamorphic history. The primary stage of this rock might be represented by the assemblage of glaucophane + epidote + titanite ± paragonite. The assemblage yields 1.7 - 1.0 GPa in assumed temperature of 300 - 550 °C, which is interpreted as maximum pressure limit of prograde stage. The peak P-T condition estimated on the basis of the equilibrium of garnet rim, barroisite, phengite, epidote, and quartz, yields 547 - 690 °C and 1.1 - 1.5 GPa on the albite epidote amphibolite-facies that correspond to the depth of 38 - 50 km. The retrograde stage was presented by changing mineral compositions of amphiboles from the Si-rich barroisite to the actinolite, which lies near 0.5 GPa at 350 °C. It could be concluded that metamorphic rocks from the Meratus Complex experienced low-temperature and high-pressure conditions (blueschist-facies) prior to the peak metamorphism of the epidote amphibolite-facies. The subduction environments in Meratus Complex during Cretaceous should be responsible for this metamorphic condition.